2020
DOI: 10.26434/chemrxiv.12003930.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of FDA Approved Drugs Targeting COVID-19 Virus by Structure-Based Drug Repositioning

Abstract: <p>The new strain of Coronaviruses (SARS-CoV-2), and the resulting Covid-19 disease has spread swiftly across the globe after its initial detection in late December 2019 in Wuhan, China, resulting in a pandemic status declaration by WHO within 3 months. Given the heavy toll of this pandemic, researchers are actively testing various strategies including new and repurposed drugs as well as vaccines. In the current brief report, we adopted a repositioning approach using insilico molecular modeling screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
10
2
Order By: Relevance
“…Comparative analysis of the affinity tendency observed for three of the 12 evaluated compounds previously reported by Farag et al (Darunavir > rosuvastatin > saquinavir) [8], Chen et al (ledipasvir > velpatasvir) [9], Adem et al (hesperidin > rutin > diosmin) [35], and Kumar et al (tipranavir > raltegravir) [10] revealed discrepancies when compared with our findings. These observations highlight the degree to which the computational strategy employed to identify potential inhibitors of SARS-CoV M pro impacted affinity tendency, and underscored the utility of combining docking, MD simulations and end-point binding free energy methods.…”
Section: Free Energy Of Bindingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of the affinity tendency observed for three of the 12 evaluated compounds previously reported by Farag et al (Darunavir > rosuvastatin > saquinavir) [8], Chen et al (ledipasvir > velpatasvir) [9], Adem et al (hesperidin > rutin > diosmin) [35], and Kumar et al (tipranavir > raltegravir) [10] revealed discrepancies when compared with our findings. These observations highlight the degree to which the computational strategy employed to identify potential inhibitors of SARS-CoV M pro impacted affinity tendency, and underscored the utility of combining docking, MD simulations and end-point binding free energy methods.…”
Section: Free Energy Of Bindingcontrasting
confidence: 99%
“…in previous studies that virtually screened candidates targeting monomeric SARS-CoV2 M pro[8][9][10][11]. Of the 12 FDA approved drugs identified, darunavir, indinavir, saquinavir and tipranavir are HIV protease inhibitors, and…”
mentioning
confidence: 99%
“…Some of the small molecule medicines used in our docking study were previously reported in other computational studies. [15][16][17][18] Autodock was the program we adopted for the docking analysis. 21 The covalent ligand and non-bonded small molecules in the structure of 6LU7 was removed for the preparation of the protein structure for the docking.…”
Section: Resultsmentioning
confidence: 99%
“…Since the release of the first M Pro crystal structure, many computational studies have been carried out to screen existing drugs in their inhibition of M Pro and many potent leads have been proposed. [15][16][17][18] However, most of these lead drugs have not yet been confirmed experimentally. To investigate whether some existing drugs can potently inhibit M Pro , we have docked a group of selected FDA/EMA-approved small molecule medicines to the active site of M Pro and selected about 30 hit drugs to characterize their inhibition on M Pro experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been recently reported that nelfinavir had anti-SARS-CoV-2 activity, as demonstrated in a cell-based experimental assay [12,13]. In addition, other HIV protease inhibitors such as indinavir, darunavir, and saquinavir, have been proposed as drug candidates against SARS-CoV-2 M pro , using computational studies [14][15][16][17][18]. These HIV protease inhibitors are repurposed drug candidates, some of which are already being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%